Peningkatan Intensi Anak Magang untuk Bekerja di Hotel Aryaduta Medan - Efin Shu (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
The hospitality industry is growing rapidly, driven by global tourism and increasing service demand. The rapid growth of the tourism industry has also encouraged the emergence of tourism schools that aim to produce skilled workers in this field. However, only 30% of tourism and hospitality school graduates work in the industry. Most graduates are not interested in pursuing a career in the hospitality industry after they complete their internship program or graduate from college. This PKM aims for the leaders of the Aryaduta Medan Hotel department to better understand: (1) things that cause graduates to be uninterested in pursuing a career in the hospitality industry (2) ways to increase the intention of interns to pursue a career in the hospitality industry. To achieve this goal, the resource person collaborated with Hotel Aryaduta Medan in the seminar “Increasing the Intention of Interns to Work at Hotel Aryaduta Medan” to explain this. The seminar will begin with a presentation session by the resource person, followed by a focus group discussion session, and close with a conclusion and recommendations session. Based on the results of the focus group discussion, it was found that the causes of the low intention of interns to work in the hospitality industry were their personality did not match the work culture at the hotel, overtime hours, and lack of balance between personal life and work. Hotel management is advised to conduct a feedback questionnaire to better understand the personality and challenges faced by interns. Management as practitioners could collaborate with schools to provide a preview of works at a hotel in one or several lecture sessions. Management is also advised to reduce overtime hours and provide a proportional workload for interns.